Innovating coatings at Nipo International - CRAMA, Pascale (Institutional Knowledge at Singapore Management University, 2022)
This case study is set in November 2021. It describes how Amanda Khoo, Director of Nipo International (Nipo), had been exploring ways to innovate and expand the company’s core product that was bitumen-based coatings. Khoo had led Nipo to embark on its innovation journey for more than 20 years. In the last 10 years, Khoo had been collaborating with several research institutes in Singapore including the Agency for Science, Technology and Research (A*Star), Nanyang Technological University (NTU) and National University of Singapore (NUS) on four innovation projects. After a multi-year journey of research and development (R&D), Nipo had a few promising products to show. However, these products were still undergoing field trials as at November 2021. The outlook for Nipo’s focused industry – the construction industry, was predicted to be promising for the next 30 years. What should Khoo do to further drive innovation and commercialise the products? Students will be able to 1) apply the concept of analogies to drive innovation in an organisation, 2) understand how boundary spanners can enable technology transfer across organisational boundaries, 3) evaluate the success of innovations, and 4) learn about how to commercialise products.